Coley’s Toxin to First Approved Therapeutic Vaccine—A Brief Historical Account in the Progression of Immunobiology-Based Cancer Treatment - K. Devaraja; Manisha Singh; Krishna Sharan; Sadhna Aggarwal (Biomedicines)
Cancer immunobiology is one of the hot topics of discussion amongst researchers today, and immunotherapeutic modalities are among the selected few emerging approaches to cancer treatment that have exhibited a promising outlook. However, immunotherapy is not a new kid on the block; it has been around for centuries. The origin of cancer immunotherapy in modern medicine can be traced back to the initial reports of spontaneous regression of malignant tumors in some patients following an acute febrile infection, at the turn of the twentieth century. This review briefly revisits the historical accounts of immunotherapy, highlighting some of the significant developments in the field of cancer immunobiology, that have been instrumental in bringing back the immunotherapeutic approaches to the forefront of cancer research. Some of the topics covered are: Coley’s toxin—the first immunotherapeutic; the genesis of the theory of immune surveillance; the discovery of T lymphocytes and dendritic cells and their roles; the role of tumor antigens; relevance of tumor microenvironment; the anti-tumor (therapeutic) ability of Bacillus Calmette– Guérin; Melacine—the first therapeutic vaccine engineered; theories of immunoediting and immunophenotyping of cancer; and Provenge—the first FDA-approved therapeutic vaccine. In this review, head and neck cancer has been taken as the reference tumor for narrating the progression of cancer immunobiology, particularly for highlighting the advent of immunotherapeutic agents.